Math, asked by sanjusanjay9255, 1 year ago

if bx + ay = a2 + b2 & ax- by = 0 then the value of x-y is........

Answers

Answered by rathin2
3
(b-a) (a2+b2)/(a sq+b sq) is the answer
Answered by Anonymous
4

Step-by-step explanation:

b \times  \: + \: ay \:  = a {}^{2}  + b {}^{2}.......(1)

ax \: - \: by \: = 0......(2)

Now \: \\  re - arranging \:  both \:  the \:  equation \:  in  \: ax+

by+c=0 form: \\ </p><p>bx+ay−(a </p><p>2</p><p> +b </p><p>2</p><p> )=0 ....(3) \\ </p><p>ax−by+0=0 .....(4)

From \:  equation  \: (3)  \: and  \: (4) \:  will  \: get

a {}^{1} = \: b, \: b {}^{1}  = a, \: c {}^{1}  =  - (a {}^{2}  + b {}^{2} )

a {}^{2}  = a,b² = -b, c² = 0

Now \: applying \: cross \: multiplication:

 \frac{ \times }{b¹c² \:  - \:   b²c¹}  =  \frac{y}{c {}^{1}a² \:  - c²a¹ } = \:  \frac{1}{a¹b² \:  - a²b¹ }

(b) \:  \frac{ \times }{(0) -( - b) \: ( -a² - \: b²) }  =

 \frac{y}{(-a² \:  - b²)a - 0 (b)}  =  \frac{1}{b(-b) \:  - a(a)}

⇒  \frac{ \times }{0 +b(a² -b²)  }  =  \frac{y}{(-a² - b²)a - 0}  =  \frac{1}{-a² -b² }

⇒ \frac{x}{b( -a² -b²)  }  =  \frac{1}{ - a² - b² }

⇒x = b

⇒ \frac{y}{(-a²-b²)a} = \:  \frac{1}{ - a²-b²}

⇒y = a

Hence, x−y⇒b−a

Similar questions